From humanizing principles to humanizing practices: Exploring core practices as a bridge to enacting humanizing pedagogy with multilingual students. (May 2022) - Peercy, Megan Madigan; Tigert, Johanna; Fredricks, Daisy; Kidwell, Tabitha; Feagin, Karen; Hall, Wyatt; Himmel, Jennifer; DeStefano Lawyer, Megan
Abstract: Humanizing approaches to the education of multilingual students have been limited by scholarship that lacks an empirical basis or clear implications for teacher education, making it challenging for teacher education programs to support teachers' enactment of equitable practice with multilingual students. We argue that although core practices have been criticized for marginalizing issues of justice, they may provide a bridge from humanizing principles to humanizing practices. Drawing on novice teachers' enactment of some of the core practices we have identified, we suggest that with further development these core practices have potential to humanize the teaching and learning of multilingual students.